HUBUNGAN FAKTOR RISIKO USIA KEHAMILAN DAN RIWAYAT ABORTUS DENGAN KEJADIAN ABORTUS INKOMPLIT DI RSUD TENRIAWARU - Indryani; mustar; Hasnidar; Nuralim (Jurnal Suara Kesehatan, 2023)
Abstract. Incomplete abortion (miscarriage) is diagnosed when part of the products of conception have been born or can be felt in the vagina but some are still left, usually placental tissue. Bleeding usually continues profusely and can harm the mother. The uterine ossium often remains open because there are still objects in the uterus which are considered foreign bodies (corpus allineum), so the uterus will try to expel them by contracting so that the mother feels pain, incomplete abortion which is not treated quickly can be life threatening for both the mother and the fetus. The purpose of this study was to determine the relationship between risk factors for gestational age and history of abortion with the incidence of incomplete abortion. The type of research used is quantitative research with analytic cross-sectional design, univariate analysis is carried out on the variables from the research results. In this analysis only produces the distribution and percentage of each variable, and cross-analysis is carried out using cross tables known as rows x columns (B x K ), so that it is known whether or not there is a statistically significant relationship. Hypothesis testing was carried out using the Chi-square test with the SPSS (Statistical Product and Service Solution) computer program version 16. The decision to test the hypothesis was based on a significance of 95% (p <0.05), the results based on the statistical chi-square test that had been carried out showed that p.value 0.001 (p < 0.05) The research hypothesis Ha is accepted which states that there is a relationship between gestational age and the incidence of abortion, the results of the analysis obtained a p value > 0.05 (0.15 > 0.05), which means that the history of abortion is not significant with incomplete abortion. Suggestions in the study are that pregnant women routinely carry out antenatal care examinations at least 4 times during pregnancy. Abstrak. 9 Abortus inkomplit (incomplete abortion / miscarriage) didiagnosis bila sebagian hasil konsepsi telah lahir atau teraba di vagina tetapi sebagian masih tertinggal, biasanya jaringan plasenta. Perdarahan biasanya terus berlangsung banyak dan dapat membahyakan ibu. Ostium uteri sering kali tetap terbuka karena masih ada benda didalam rahim yang dianggap sebagai benda asing(corpus allineum), sehingga uterus akan berusaha mengeluarkannya dengan berkontraksi sehingga ibu merasa nyeri, abortus inkomplit yang tidak ditangani dengan cepat dapat mengancam jiwa baik bagi ibu maupunjaninnya. tujuan penelitian ini untuk mengetahui Hubungan Faktor risiko Usia kehamilan dan Riwayat abortus dengan kejadian abortus inkomplit. Jenis penelitian yang digunakan penelitiaqn kuantitatif dengan desain cross sectional analitik, Analisis univariat dilakuan terhadap variabel dari hasil penelitian Dalam analisis ini hanya menghasilkan distribusi dan presentase dari tiap variable, serta Analisa silang dilakukan dengan menggunakan tabel silang yang dikenal dengan baris x kolom (B x K), sehingga diketahui ada atau tidak ada hubungan yang bermakna secara statistik. Uji hipotesis dilakukan menggunakan Chi-square test dengan program computer SPSS (Statistical Product and Service Solution) versi 16. keputusan pengujian hipotesis didasarkan atas signifikasi 95 % (p < 0,05), hasil penelitianberdasarkan uji statistic chi-square yang telah dilakukan menunjukkan p.value 0,001 (p < 0,05) Hipotesa penelitian Ha diterima yang menyatakan bahwa ada hubungan usia kehamilan dengan kejadian abortus, hasil analisis didapatkan nilai p > 0,05 (0,15 > 0,05) yang artinya riwayat abortus tidak signifikan dengan kejadian abortus inkomplit. Saran dalam penelitian diharapkan ibu hamil rutin melakukan pemeriksaan antenatal care minimal 4 kali selama kehamilan.